PENGARUH PERSEPSI HARGA, CITRA MEREK DAN MOTIVASI TERHADAP KEPUTUSAN MEMILIH KULIAH DI STEIN JAKARTA - Meylani Tuti (Panorama Nusantara, 2020)
The purpose of this research is to find out the influence of price, brand equity and motivation to purchase decision. Population of this research are STEIN students from the 1st semester to the 7th semester. Sampling Technique being used is accidental sampling with the number of sample of 296 respondents. Data collection method is using questionnaires distributed to respondents and has been tested for the validity and reliability. Data analysis is done by descriptive and quantitative. The quantitative analysis is using Structural Equation Modeling (SEM). The result of the research shows that price gives significant influence towards trust by the t-value of 3.10 and it has a medium relationship with a correlation value of 0.66, while brand equity does not give influence towards purchace decision with t-value at 1.86 and owns a medium relationship with a correlation value of 0.68, and motivation gives significant influence towards purchase decision with the t-value of 7.83 and has got a very strong relationship with a correlation value of 0.91.